THE GREATER BLACK SEA REGION— A GATEWAY TO EURASIA - ZAZHIGAEV, Boris (CENTRAL ASIA AND THE CAUCASUS, 2011)
At all times the Black Sea Region has played an important role in the life of the Eurasian people; it was on the shores of the Black Sea those great empires flourished and disappeared. Today, it is the source of the worst threats of the 21st century that still linger in the larger part of the post-Soviet expanse; it is also a seat of “frozen conflicts” largely associated with instability in the Greater Middle East. The present political and ideological contradictions in the region interfere with the eastward progress of liberal and democratic values. Despite all sorts of external and internal threats, the Greater Black Sea Region (a triangle formed by Russia, Europe, and the Islamic world) so far remains a relatively calm area, most of the states of which are distinguished by a European foreign policy vector. When looking at part of the Black Sea Region and the Caucasus (together with Central and part of South Asia) as a geopolitical segment of the Persian Gulf states and the Middle East, Brzezinski called it the “Eurasian Balkans” and believed that the term “power vacuum” described the situation to a tee.1 The Black Sea Region and its unique natural and man-made strategic facilities occupy a highly advantageous geopolitical place on the globe. The Crimean Peninsula, which in the late 1980s and early 1990s was a target of fierce contention, should be mentioned in particular. The region’s geopolitical potential and the dynamics of global evolution have turned it into a subject for scientific scrutiny, largely prompted by the novelty of the problems created by the processes unfolding before our eyes.